Coasis a coconut themed detox and wellness resort spa - Rivera, Rosenda Lea G.; Litonjua, Emmanuel A. (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
Coconut being called as the "tree of life" has a lot of benefits that is seen to bring the country into a lot of possibilities. The purpose of this thesis was to showcase these abundant uses through designing a facility that will boost coconut as an exceptional gift of nature to man and speak out to the world its significant value. The overall approach was to come up with a wellness and detox resort spa that will support tourism and at the same time support the growth of Philippine coconut industry. It highlighted the different coconut by-products including the in demand Virgin Coconut Oil and Hydrating Coconut Water, as well as building materials such as cocofiber and cocowood. Aside from the wellness facility, the development was completed through designing other special structures that celebrate the spirit of Filipino craftsmanship and ingenuity which were also inspired by the tree. Delivered with pleasant wellness services and facilities, Coasis serves as a retreat of calm in the city. Upon completion of the research and design, it is found that coconut is indeed a magical fruit as countless possible means and materials can be sourced out of it especially in designing a good wellness architecture and development.
Includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Coasis (Spa); Health resorts -- Designs and plans